Refugees' right to health: A case study of Poland's disparate migration policies - Kędziora, Krzysztof (Bioethics, 2025)
Poland has faced two waves of migration: the first was of irregular asylum seekers, which led to the humanitarian crisis on the eastern EU–Belarusian border since 2021; the second was of Ukrainians fleeing the Russian invasion. Although there are noticeable differences between these situations, and between the different reactions of the Polish authorities, it is possible to juxtapose them in terms of the right to health. The normative content of refugee and human rights law is the starting point for reconstructing the meaning of the terms ‘refugee’ and ‘right to health’. A refugee is a person who needs international protection because of a well-founded fear of harm, which is not limited to persecution as defined by the Refugee Convention but also includes situations of international and non-international armed conflict. The right to health, which includes, inter alia, entitlements to a ‘system of health protection’ and ‘underlying determinations of health’, is reconstructed on the basis of human rights law and refugee and migration law. There are no legal and moral grounds to grant the right to health differentially to different groups of refugees. Nondiscriminatory health policy requires that refugees have the same access to health care as nationals, although their specific health needs resulting from past experiences and refugee situation require special treatment, that is, an appropriate refugee health policy. The broad understanding of the underlying determinants of health demonstrates the importance of overall migration policy for refugees’ health, which can jeopardise the fragile good of refugee health.